2016
DOI: 10.4077/cjp.2016.baf444
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Effects of Chronic Intermittent Hypobaric Hypoxia on Renal Vascular Hypertension through Enhancing Baroreflex

Abstract: Baroreflex function plays a critical role in the maintenance of cardiovascular homeostasis and is impaired in different types of hypertension in both human and animals. Chronic intermittent hypobaric hypoxia (CIHH) facilitates baroreflex in anesthetized rats. The aim of present study was to investigate the effect of CIHH on arterial blood pressure (ABP) and baroreflex function in renal vascular hypertension (RVH) rats. Adult male Sprague-Dawley rats were randomly divided into four groups: Sham-operated (SHAM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Our previous studies have shown that CIHH facilitates the baroreceptor reflex and enhances the stable reduction of fluctuations in BP [7]. Recently, we confirmed that CIHH enhances baroreflex sympathetic inhibition, facilitates the baroreceptor reflex, and antagonizes the impaired baroreceptor reflex function in renal hypertensive rats [6]. The present study further investigated the central mechanism of the CIHH anti-hypertension effect and focused on the NTS in RVH rats.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Our previous studies have shown that CIHH facilitates the baroreceptor reflex and enhances the stable reduction of fluctuations in BP [7]. Recently, we confirmed that CIHH enhances baroreflex sympathetic inhibition, facilitates the baroreceptor reflex, and antagonizes the impaired baroreceptor reflex function in renal hypertensive rats [6]. The present study further investigated the central mechanism of the CIHH anti-hypertension effect and focused on the NTS in RVH rats.…”
Section: Discussionsupporting
confidence: 51%
“…It has been reported that chronic intermittent hypobaric hypoxia (CIHH) decreases arterial blood pressure (ABP) in patients with essential hypertension and in spontaneously hypertensive rats [4,5]. Our previous study demonstrated that CIHH decreases ABP in rats with renovascular hypertension (RVH) [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has demonstrated the benefits of chronic intermittent hypobaric hypoxia (CIHH) on multiple organs of the body such as heart, brain, liver, and kidney [ 15 18 ], including regulating immune system, anti-collagen-induced arthritis [ 19 ], antihypertensive activity [ 15 ], and improving dyslipidemia and glucose tolerance in type 2 diabetes [ 16 ] . Recently, it was reported that CIHH had an anti- aplastic anemia eect through improving the adhesiveness and stress of mesenchymal stem cells [ 20 ], and a modulating effect on brain iron homeostasis in rats [ 18 ] .…”
Section: Introductionmentioning
confidence: 99%
“…A rat model investigated the effect of chronic intermittent hypobaric hypoxia (CIHH) on arterial blood pressure (ABP) and baroreflex function in renal vascular hypertension (RVH). According to the model, CIHH resulted in the recession of renovascular hypertension through the facilitation of a baroreflex control [ 83 ]. Moreover, the beneficial impact of radiation was shown in nephrectomized rats that achieved better blood pressure control and proteinuria levels, compared to their controls [ 84 ].…”
Section: Introductionmentioning
confidence: 99%